EGFR bypass activation mediates acquired resistance to regorafenib in hepatocellular carcinoma - Hu, Lili; Shi, Weiwei; Liu, Kua; Ma, Ding; Xin, Qilei; Wang, Zhongxia; Cao, Yin; Zhang, Guang (Frontiers in Medicine, 2024)
Background: Regorafenib, a tyrosine kinase inhibitor (TKI), is used in the treatment of unresectable hepatocellular carcinoma (HCC). However, the occurrence of acquired resistance limits its antitumor efficacy. While multiple studies have highlighted the crucial role of bypass activation in acquired TKI resistance, few have focused on bypass activation in regorafenib resistance in HCC.Methods: High-throughput proteomics was used to identify differential proteins associated with bypass activation between acquired regorafenib-resistant cells and parental cells. The ability of epidermal growth factor receptor (EGFR) bypass inhibition to reverse resistance was evaluated both in vitro and in vivo using direct microscopic observation, the CCK-8 assay, colony formation assay, Annexin V-FITC/propidium iodide double staining, cell cycle analysis, western blotting, and a xenograft model.The expression of EGFR, a member of the receptor tyrosine kinase (RTK) family, was significantly increased in acquired regorafenib-resistant HCC cells compared with parental cells. Pharmacological inhibition of EGFR with gefitinib restored the sensitivity of regorafenib-resistant HCC cells to regorafenib. In a xenograft mouse model, gefitinib sensitized resistant tumors to regorafenib.Additionally, levels of RAS, RAF, and P-ERK1/2, components of the downstream EGFR signaling pathway, were positively associated with EGFR expression.Conclusions: EGFR overexpression promotes acquired resistance to regorafenib through RAS/RAF/ERK bypass activation in HCC. Inhibition of EGFR restores 4 sensitivity to regorafenib, and the combination of gefitinib and regorafenib demonstrates significant antitumor efficacy both in vivo and in vitro. These findings suggest that this combination could be a potential strategy for patients with advanced HCC.